Maximal power and performance during a swim taper - Trinity, J. D.; Pahnke, M. D.; Sterkel, J. A.; Coyle, E. F. (International Journal of Sports Medicine, 2008)
This study examined how altering training intensity during a taper impacts maximal mechanical power (Pmax), torque at power maximum (T), velocity at power maximum (V), and swim performance (m · sec-1). Using an arm ergometer with inertial loading, measurements of Pmax, T, and V were made for 7 consecutive weeks prior to the taper and during the taper in 7 female competitive collegiate swimmers. Subjects were tested over two consecutive years. Swim performance was obtained from 3 competitive meets; a conference meet (CM), the conference championship meet (CONF) and the national championship meet (NAT). A 50 to 60 % increase in the amount of "high-intensity training" during the taper of 2005 (High-Intensity Taper - HIT) resulted in Pmax values that were 8 to 14 % higher (40 to 60 Watts) at all but one time point when compared to the 2004 taper (Low-Intensity Taper - LIT). Swim performance was significantly worsened at the NAT following LIT. However, with the HIT, swim performance, Pmax, and T were maintained prior to and at NAT. A large reduction in high-intensity training during a taper reduces the length of time that Pmax, T, and swim performance can be maintained at peak levels.